PERTANGGUNGJAWABAN PIDANA BAGI PENGIDAP NECROPHILIA DALAM TINDAK PIDANA PEMERKOSAAN MAYAT - Siahaan, Vania Romasta; Gita Rismawati,; Mardian Putra Frans, (The Juris, 2024)
This research examines necrophilia as a sexual orientation deviation that has not been regulated in the National Criminal Code. The National Criminal Code Article 271 focuses on corpses, digging up or dismantling graves, taking, moving or transporting corpses and treating corpses in an uncivilized manner while the rape of corpses is not regulated in the National Criminal Code. Thus, there is a legal vacuum. This is a new problem because the status of necrophilia is mentioned as a form of disease so how is the form of responsibility. The purpose of this study is to find out how the regulation and form of criminal liability for perpetrators who have necrophilia in the crime of corpse rape. The research method used in this writing is juridical-normative legal research, using a statutory approach in order to discuss legal issues in this research. The results of this study found that criminal liability for people with necrophilia in the crime of corpse rape is basically not clearly regulated in the new Criminal Code. From the perspective of criminal acts, it is regulated in Article 271 of Law Number 1 Year 2023 (National Criminal Code) and from the perspective of the crime of rape, it is formulated in Article 415 of the National Criminal Code. While the crime against the corpse itself is regulated in Article 415 of the National Criminal Code and Article 271 of the new Criminal Code, Article 269 of the National Criminal Code and Article 270 of the National Criminal Code.